Letter (copy) : S.S. "Yorkbrook" - Citrine, Walter, 1887-1983
011-0106-001 EB/IS/IB WMC/WJB/AC/588 International 24th March, 1937. Mr. Ernest Bevin, Transport & General Workers' Union, Transport House, LONDON. S.W. 1. Dear Mr. Bevin, S.S. "YORKBROOK". I have duly received your letter of 23rd instant, and thank you for the information contained therein relative to the above ship. Yours faithfully, General Secretary. 292/946/11/106